2019
DOI: 10.1002/app.48469
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance PA1/TPU films with enhanced dielectric constant and low loss tangent

Abstract: Polymer composites with high dielectric constant are promising materials for energy-storage application. However, their development has generally been hindered due to the challenge to balance dielectric constant and loss tangent. In this work, a novel thermoplastic polyurethane (TPU)-based composite with high dielectric constant and low loss tangent was prepared by inducing polyamide-1(PA1). The optimal content of PA1 in TPU matrix was 1.0 wt %. Importantly, the dielectric constant of TPU exhibited great stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…There are few reports investigating all-organic PS-based composites. In comparison to PS-based inorganic composites, all-organic PS films display the advantages of being lightweight and having a good processability and flexibility. For example, Ploehn et al fabricated di-block copolymer films consisting of π-conjugated terthiophene-containing methacrylate and PS (PTTEMA- b -PS) and PTTEMA/PS blending films with the same mass fractions of PTTEMA. The experimental results showed that both PTTEMA- b -PS copolymers and PTTEMA/PS blends exhibited linear polarization behavior and low hysteresis.…”
Section: Introductionmentioning
confidence: 99%
“…There are few reports investigating all-organic PS-based composites. In comparison to PS-based inorganic composites, all-organic PS films display the advantages of being lightweight and having a good processability and flexibility. For example, Ploehn et al fabricated di-block copolymer films consisting of π-conjugated terthiophene-containing methacrylate and PS (PTTEMA- b -PS) and PTTEMA/PS blending films with the same mass fractions of PTTEMA. The experimental results showed that both PTTEMA- b -PS copolymers and PTTEMA/PS blends exhibited linear polarization behavior and low hysteresis.…”
Section: Introductionmentioning
confidence: 99%
“…Breakdown strength ( E b ) is a key factor to achieve a high energy density of dielectric capacitors. Figure a displays the E b of the PPDI/PVTC blending films with various loadings of PPDI, which is investigated by a two-parameter Weibull statistic distribution method as below …”
Section: Resultsmentioning
confidence: 99%
“…Reproduced with permission. [ 66 ] Copyright 2020, WILEY. c) The schematic diagrams of PAQS and various properties of PVDF/PAQS blend films.…”
Section: Architectures For Polymer Dielectricsmentioning
confidence: 99%